Iberische Halbinsel: Antike Hafenanlagen auf der iberischen Halbinsel - Hermanns, Marcus H. (e-Forschungsberichte des DAI, 2023)
In 2014, the catalogue of contexts concerning harbours and anchorages on the Iberian Peninsula was completed. Five categories were distinguished: harbour facilities, port towns, anchorage grounds, other nautical infrastructure and ship-wrecks. All data was processed for iDAI.gazetteer and linked within iDAI.bibliography/ZENON. The project is part of DAI Cluster VI, working group „Hafenorte“.